Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
you will have to complete the square
factor the 4 out of the first two terms
y = 4(x^2 - 2x) + 5
x^2 - 2x + 1 = (x - 1)^2
we want what we have to look like this
the difference between (x^2 - 2x) and (x^2 - 2x + 1) is the +1
so we add a 1 and subtract a 1 to keep balance
y = 4(x^2 - 2x + 1 -1) + 5
y = 4(x^2 - 2x + 1) - 4 + 5 [moved the extra -1 out of it and distributive property]
y = 4(x - 1)^2 + 1 [factored and added like terms]
y = 4(x-1)^2 + 1
or
y - 1 = 4(x-1)^2
is now in vertex form.
factor the 4 out of the first two terms
y = 4(x^2 - 2x) + 5
x^2 - 2x + 1 = (x - 1)^2
we want what we have to look like this
the difference between (x^2 - 2x) and (x^2 - 2x + 1) is the +1
so we add a 1 and subtract a 1 to keep balance
y = 4(x^2 - 2x + 1 -1) + 5
y = 4(x^2 - 2x + 1) - 4 + 5 [moved the extra -1 out of it and distributive property]
y = 4(x - 1)^2 + 1 [factored and added like terms]
y = 4(x-1)^2 + 1
or
y - 1 = 4(x-1)^2
is now in vertex form.
a=4, b=-8, c=5
h=-b/2a= -(-8)/2(4)
8/8=h=1
K= a(h)^2+b(h)+c
K= 4(1)^2-8(1)+5
K= 4-8+5
K= 1, Vertex Form: a(x-h)^2+k
Vertex Form: Y= 4(X-(1)^2+K
Y= 4(x-1)^2+1
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.